Cohesion, style, and ecological consciousness in Bassey’s “Return to Being” - Latif Razak; Jonathan Essuman; Faith Ben-Daniels; Rita Ndonibi (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2026)
Discourse-stylistic devices are crucial in creating meaning and coherence in poetry. Studies in the discourse stylistics of poetry remain limited, with most existing studies focusing on the genre's stylistic aspects. Thus, this study is among the first to examine Nnimmo Bassey’s eco-poem “Return to Being” through a discourse-stylistic approach. Drawing on Halliday and Hasan’s (1976) cohesion framework and Leech and Short’s (2007) stylistic model, the study explored how the use of cohesive devices and stylistic choices contributes to the poem’s environmental message. The findings revealed that grammatical and lexical cohesive devices were used to enhance the poem's coherence. The grammatical cohesive devices found include reference and conjunction, while substitution and ellipsis were absent. Again, lexical cohesion was achieved through repetition, synonyms, antonyms, hyponyms, and collocations. Moreover, Bassey employed stylistic features, including grammatical categories and figures of speech, to highlight the devastation of the Niger Delta's natural environment and to call for its restoration. The findings deepen our understanding of the use of discourse-stylistic devices in eco-poetry.